Sejarah Konflik di Suriah: Sosok Tokoh Hafez al-Assad dan Bashar al-Assad - Muh. Taufiq Syam; Hasaruddin (CARITA: Jurnal Sejarah dan Budaya, 2023)
The protest movement against the government regime that took place in the peninsular region of the Arabian peninsula, helped initiate the birth of conflict in Syria. On the one hand, there are also claims that this conflict was triggered by conflict between Shia-Sunni groups between the government involving the central figures Hafez al-Assad and Bashar al-Assad and the opposition groups. Therefore, the purpose of this research is to find out the historical background of the birth of the conflict in Syria and the extent of the main roles of Hafez al-Assad and Bashar al-Assad in the history of the conflict that occurred in Syria. This study used a literature review method with a descriptive analysis approach. The literature that discusses the Arab Spring and the history of the Syrian conflict is the main study material to answer the problem formulation in this paper. In the final stage, this research will present conclusions from the discussion and implications of the background causes of the conflict in Syria.